Siluro-Devonian palaeomagnetism, terrane emplacement and rotation in the Caledonides of western Ireland - Piper, J. D. A. (Geophysical Journal International, 1991)
The palaeomagnetism of a Silurian succession (Lough Mask Formation lavas and sediments) and intrusive rocks (Kilbride dolerites and andesites and microgranodiorites, Killary Harbour area) in the Connemara-Mayo segment of the Irish Caledonides is described. Magnetizations are related to the regional tectonic history with the aid of fold, conglomerate and contact tests. They describe sequences of shallow to intermediate inclinations in both the eastern and western sectors of this Caledonian inlier. The shallow components appear to pre-date Siluro-Devonian folding while the intermediate ones post-date this episode. The change in palaeofield inclination is identical to the transition described by contemporaneous deep level (Silurian) to shallow and surface level (Lower Devonian) bodies in the British and Scandinavian Caledonides but declinations are rotated consistently to the west. The Lower-Middle Silurian vector is rotated clockwise by c. 100°. This difference is progressively reduced to c. 50° by the time of the Siluro-Devonian D2 folding, showing that this fold generation (now oriented E-W) developed in parallelism with contemporaneous folds on the NE strike continuation of the Caledonides. Post-folding remanences continue to deviate in a clockwise sense from the remainder of the Caledonides showing that rotation continued into Middle-Upper Devonian times and finally ceased during Carboniferous times. The integrated effect of this rotation is recognized in Ordovician magnetizations from the Dalradian metamorphic terrane of south Connemara. It can be explained by block rotations within a zone of distributed deformation according to the McKenzie-Jackson model and illustrated by many neovolcanic zones. Palaeomagnetism defines a tectonic regime commencing with rotations of c. 3° Myr−1 and lasting from mid-Silurian to Carboniferous times. Western Ireland is sited within a closure gap along the Iapetus suture extending from Ireland to Newfoundland, and these terranes were apparently emplaced by progressive ...